The Relationship between Preschool Experiences and Attainment of Literacy Skills in Kindergarten - Zapf, Shawn (My University, 2019)
The purpose of this action research was to determine whether students with and without early school experience performed similarly in terms of meeting end of year kindergarten expectations in the area of pre-reading skills. This causal-comparative study used data from a school system’s county’s assessment system, which measured students’ levels of pre-reading skills in the areas of alphabetical principles and sight words with the Kindergarten Literacy Assessment (KLA) assessment. Three hypotheses were tested to determine whether students had significantly different KLA scores and pass rates across their preschool experiences. The results indicated that the only significant difference was between the groups’ mean fall KLA scores. End of year kindergarten instructional scores and pass rates were only slightly higher for those with preschool experience compared to those without. No statistically significant difference was found in the fall or spring KLA pass rates or scores for the groups who received interventions across preschool experience conditions. Further research appears warranted to determine what aspects of preschool improve students’ readiness for school and how to maintain those benefits.
Keywords: Education -- Research papers (Graduate).